Design And Analysis Of Electronic Measurement Circuits Of Invasive Electrical Capacitance Tomography In Identifying Oil-Gas Regime For Conducting Pipe Application - Haziq Syakir, Hamzah (2022)
This project is to investigate the changes of capacitance value due to the changes of permittivity distribution of different dielectric materials such as water and oil in conducting pipeline using invasive approach of electrical capacitance tomography (ECT). In this project, 8 electrodes of ECT system are developed. Also, the signal generator circuit at the transmitter channel and the amplifier circuit at the receiver were developed. The sensor jig is developed in order to obtain the electrical potential distribution between electrode. A several position, sizes and multiple obstacles as obstacle in oil medium were tested in this paper. The sensor performance inside the sensor jig was analyzed and the data was collected. The data was then used to reconstruct image using the Linear Back Projection Method through COMSOL and MATLAB software. The tomogram was obtained and compared using the MSSIM index to determine the accuracy of the image created. The minimum size that can detect is 33mm in diameter, whereby it shows the higher MSSIM index if compared to the 20mm and 25mm obstacles. Also, the tomogram created by the 33mm obstacle had a better-quality image. In short, the invasive approach for ECT is seen possible to be applied for oil-gas application in steel pipe.